Pendidikan Matematika Realistis untuk Penalaran Logis Siswa Sekolah Dasar - Windari, Reza Aulia; Amir, Mohammad Faizal (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
Logical reasoning for primary school students is still relatively low. Meanwhile, primary school students need logical reasoning to solve problems based on reasonable facts. Realistic mathematics education (RME) model is thought to improve students' logical reasoning. The purpose of the study was to examine the effect of RME model on logical reasoning of primary school students. A quasi-experimental design with one group pretest-posttest was applied as the research design. Meanwhile, the research sample was taken in one of the public primary schools in Sidoarjo, which was randomly selected. Data analysis techniques used descriptive and inferential. The results showed a difference in the average pretest and posttest scores on logical reasoning. Meanwhile, the paired t-test result of 0.000 <0.05 provides evidence that there is indeed a substantial relationship between the application of the RME model and the improvement of logical reasoning skills of primary school students. Thus, the RME model significantly affects the logical reasoning of primary school students.